Counseling across and beyond cultures : exploring the work of Clemmont E. Vontress in clinical practice - Walcott, Rinaldo, 1965-; Moodley, Roy (University of Toronto Press, 2010)
"Professional counseling is a dynamic field, necessarily changing to reflect shifting societal norms and client needs. In an increasingly multicultural and globalized society, there is a growing need for counselors to be sensitive to the diverse needs of clients expressing different cultural and ethnic beliefs and facets of racial, gender, sexual, age, ability, disability, or class identities.